Paranormal activity: self-control theory and belief in the paranormal - Mowen, Thomas J. (Deviant behavior, 2022)
Recent survey data show that belief in the paranormal - including aliens, ghosts, telepathy, mind reading, and unlucky numbers - is widespread in the United States. Given the ubiquitous nature of paranormal beliefs in society, insight into why individuals believe in the paranormal is surprisingly limited. Although the few studies that do exist on this topic show that paranormal beliefs vary somewhat by race/ethnicity, gender, and social class, few studies have applied a rigorous test of theory to quantitatively understand why individuals believe in the paranormal. To address this key gap in research, we use an original dataset and apply the theory of self-control to the understanding of paranormal beliefs. Overall, the data demonstrates that the majority of respondents in our sample report belief in at least one paranormal phenomenon. Multivariate analyses show that individuals with lower levels of self-control report significantly greater belief in the paranormal than those with higher self-control, even after controlling for a range of variables. The characteristics of low self-control - a tendency to choose immediately gratifying courses of action while ignoring long-term consequences - may predispose people to endorse high levels of paranormal beliefs.